A new model of school discipline : engaging students and preventing behavior problems - Dupper, David R. (New York ; Oxford : Oxford University Press, 2010)
This highly practical guide presents a transformative new model of school discipline for school personnel seeking to engage students and reduce behavior problems in the most effective pragmatic, and cost-efficient manner possible.
Includes bibliographical references and index.
Description based on print version record.
Keywords: School discipline -- United States; Rewards and punishments in education -- United States; Problem children -- United States